A sociological analysis of Iranian popular music in the 21st century - Safideh, Mohammad Rezazadeh (2015)
The main purpose of this thesis is to give a sociological explanation on what is called “Iranian popular music in 21st century” covering a period from the year 2000 to 2014. Based on reference to the history of Iranian popular music, this research aims at analyzing the nature of Iranian popular music and to find out what are the constituent elements of such social phenomenon in order to present an analytical definition of it. The other objective of this research attempts to answer the questions of what are the social factors involved in making a piece of music that is all of a sudden massively consumed in the given place and time. This thesis also endeavours the acknowledgment of social qualifications of those consuming popular music such as age group, class, taste and cultural capital available. The grounds, forms, genres and lastly contents and musical structure of popular Iranian music are also taken into consideration. Iranian underground music as opposed to legally performed popular music that is permitted by the government is also an important sociological issue about which informatory explanation is presented here. The thesis further examines the role of the music industry in production and distribution of popular music among the Iranian community in the above-mentioned period. In order to construct a sociological conceptual framework, preceding a general review of the social thoughts on the subject matter, concepts presented by three prominent music sociologists are applied. Adorno’s ‘conceptualization of market theory’, Bourdieu’s ‘conceptualization of cultural commodity consumption in relation to class taste’, and Schaefer’s ‘conceptualization on the sub-culture of youngsters’ have been selected as the road map for constructing the questions and analyzing the data gathered. Qualitative approaches for scientific investigation and semi-constructed interviews have been found most suitable as research methods for this inquiry. The tested population as the ‘focus group’ is formed by twelve [12] members of very knowledgeable and highly qualified members currently involved in the Iranian community of popular music as professors, composers, writers, critics and performers. Each of the members of the group was interviewed individually during the researcher’s fieldwork trip to Iran. The result of this investigation indicates that pop and rap genres with very simple, easy and repeatable rhythm and musical construction are currently the most popular music in Iran, and the younger generation (14–29 year old) makes the greatest number of consumers for popular music. Popular music in Iran is consumed at certain public as well as private places, individually and collectively. It is also determined that the social factors of class and cultural capital have no meaningful role for consuming popular music. The research result shows that underground music in Iran rarely shares the common attributes globally recognized as having been a sign of protest against social and political status quo. Rather, those artists who lack financial means or certain elements to create and distribute music in order to fulfil government’s provisions usually go into the underground. Some examples, however, such as few cases of politically oriented music are excluded from the general rule. In Iran, the commonly accepted definition of music industry is interpreted differently from many developed regions in the world, since some distributors ignore the law of protecting the creation of artistic works easily, duplicate and sell the products illegally in high quantities, though the main production and distribution of popular music is under the government’s management and control.